2006
DOI: 10.1007/s00535-006-1890-2
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of preoperative prediction of microinvasion of portal vein in hepatocellular carcinoma using superparamagnetic iron oxide-enhanced magnetic resonance imaging and computed tomography during hepatic angiography

Abstract: Distortion of corona, tumorous AP shunt, and tumor size are good predictors of the risk of PVI. This scoring system is simple and worth using clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 26 publications
3
46
0
Order By: Relevance
“…Recently, several reports have described peritumoral enhancement as a parameter that is suggestive of an increased risk of microvascular tumour invasion [10][11][12]. Kim et al [12] stated that irregular circumferential peritumoral enhancement is a risk factor for microvascular AFP, a-fetoprotein; HBV, hepatitis B virus; HCV, hepatitis C virus; SD, standard deviation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several reports have described peritumoral enhancement as a parameter that is suggestive of an increased risk of microvascular tumour invasion [10][11][12]. Kim et al [12] stated that irregular circumferential peritumoral enhancement is a risk factor for microvascular AFP, a-fetoprotein; HBV, hepatitis B virus; HCV, hepatitis C virus; SD, standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Miyata et al [11] reported that distortion of corona enhancement and a tumorous arterioportal shunt on CT hepatic arteriography could be significant predictors of portal vein tumour invasion. Nishie et al [10] reported that the size of the peritumoral enhancement was a significant risk factor for microvascular invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular invasion can be classified as macrovascular invasion, which involves major (first or second branches) portal or hepatic veins, and microvascular invasion, which involves third branches or microscopic vessels (9). Myata et al (10) reported that microvascular and major vascular invasions of HCC were related with a 4.4-and 15-fold increased risk of tumor recurrence, respectively. Malignant portal vein thrombus in major portal branches can be identified on Doppler ultrasound (US) or contrast-enhanced US (11,12).…”
mentioning
confidence: 99%
“…Intrahepatic recurrence is due to two mechanisms; intrahepatic metastasis (IM) originating from the primary cancer, and a second primary cancer arising from multicentric carcinogenesis (MC). IM may correlate with early recurrence and poor prognosis, whereas MC is associated with relatively good prognosis [3][4][5].…”
Section: Introductionmentioning
confidence: 99%